Crystal structure and Hirshfeld surface analysis of (E)-3-(2-chloro-6-fluorophenyl)-1-(3-fluoro-4- methoxyphenyl) prop-2-en-1-one - Hassan, Nur Hafiq Hanif; Abdullah, Amzar Ahlami; Arshad, Suhana; Khaleb, Nuridayanti Che; Razak, Ibrahim Abdul (International Union of Crystallography, 2016)
In the title chalcone derivative, C16H11ClF2O2, the enone group adopts an E conformation. The dihedral angle between the benzene rings is 0.47 (9)° and an intramolecular C-H...F hydrogen bond closes an S(6) ring. In the crystal, molecules are linked into a three-dimensional network by C-H...O hydrogen bonds and aromatic [pi]-[pi] stacking interactions are also observed [centroid-centroid separation = 3.5629 (18) Å]. The intermolecular interactions in the crystal structure were quantified and analysed using Hirshfeld surface analysis.